Lithobieae and Eriocnemeae: two new Neotropical tribes of Melastomataceae - Penneys, Darin S.; Almeda, Frank; Michelangeli, Fabian A.; Goldenberg, Renato; Martins, Angela B.; Fritsch, Peter W. (Phytotaxa, 2020)
Several genera in the Melastomataceae mostly endemic to southeastern Brazil have not been assessed for their tribal placement in a phylogenetic context. Most workers have placed the monotypic diminutive herb Lithobium in the Microlicieae, but some classifications have assigned it to either the Sonerileae or Bertolonieae. Another monotypic genus, Eriocnema, has been included in the Bertolonieae, Sonerileae, or Microlicieae. Physeterostemon contains five species, and has not previously been assigned to any tribe. Ochthephilus, a monotypic genus endemic to Guyana, was assigned to the Merianieae, but lack of fruit and seed data, and a paucity of collections, have impeded phylogenetic assessment. To assess the placement of these genera, we conducted a phylogenetic analysis of 91 species representing 73 genera from across the Melastomataceae, including 24 of the 27 putative close relatives of Lithobium, Eriocnema, Ochthephilus, and Physeterostemon and seven gene regions, i.e., the nuclear ribosomal external and internal transcribed spacer regions, and the plastid regions accD-psaI, ndhF, psbK-psbL, rbcL, and rpl16. Lithobium groups as sister to a clade comprising all non-Olisbeoideae, Pternandreae, Henrietteeae, and Astronieae tribes. A new tribe, Lithobieae, is thus created to accommodate this placement. The capsular-fruited Eriocnema, Ochthephilus, and Physeterostemon form a clade that is sister to the berry-fruited Miconieae and widely separated from tribes with which they have been associated in historical classifications. Thus another new tribe, Eriocnemeae, is created. Lectotypes are designated for E. acaulis and L. cordatum.